Lasgush Poradeci the first modern Albanian poet and the greatest lyricist of the 20th century - Muhadri, Besim (Technium Social Sciences Journal, 2023)
Lasgush Poradeci (1899-1987) is one of the most outstanding lyricists of modern Albanian poetry of the first half of the 20th century. He is the author of two poetic volumes: "Vallja e yjeve" (1933) and "Ylli i zemrës" (1937), which made him one of the most prominent Albanian lyricists. Reading and studying the work of this poet had its ups and downs over time. Although after the installation of the communist dictatorship in Albania (1955-1990) there was no proper treatment, no such thing happened in Kosovo. In addition to the publication and reprinting of his work, in Kosovo, books with studies have been written and published about his poetry. Although the list of names of researchers who have dealt with Lasgushi's work is long, in our paper we will highlight only some of the opinions of researchers such as: Rexhep Qosja, Sabri Hamiti, Emin Kabashi and Kujtim Shala.